2011
DOI: 10.1111/j.1442-2050.2010.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of lymph node metastases of esophageal squamous cell carcinoma based on the anatomical lymphatic drainage system

Abstract: The recent anatomical studies of the esophagus showed that submucosal longitudinal lymphatic vessels connect to the superior mediastinal and the paracardial lymphatics and lymphatic routes to periesophageal nodes originate from the muscle layer. Using clinical data for lymph node metastasis, we verify these anatomical bases to clarify the rational areas of lymph node dissection in esophageal cancer surgery. Analysis was performed on 356 consecutive patients who underwent esophagectomy with three-field dissecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(83 citation statements)
references
References 15 publications
6
76
1
Order By: Relevance
“…The left RLN is longer than the right RLN and is situated close to lymph node stations 2L and 4L, consequently being more at risk for injury during lymph node dissection. Meticulous dissection of these stations is pivotal since there is a high frequency of lymph node metastasis (30)(31)(32). We experience robotic assistance of great value to perform a full paratracheal lymph node clearance, which was the standard of care for all these patients (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…The left RLN is longer than the right RLN and is situated close to lymph node stations 2L and 4L, consequently being more at risk for injury during lymph node dissection. Meticulous dissection of these stations is pivotal since there is a high frequency of lymph node metastasis (30)(31)(32). We experience robotic assistance of great value to perform a full paratracheal lymph node clearance, which was the standard of care for all these patients (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…One reason for that variation could be the difference in T stage (depth of tumour invasion) of the primary tumour. It was reported that the positivity rate for locoregional nodes increases from 0% for intra-epithelial tumours to 31%-56% for T1b, 58%-78% for T2, 74%-81% for T3, and 100% for T4 tumours [14][15][16] .…”
Section: Figurementioning
confidence: 99%
“…In addition, our study observed only the distribution of metastatic lymph nodes. In fact, elective nodal irradiation should consider tumour T stage, histology, and tumour length, among other factors 15,16 . Despite those limitations, ct is an important and common tool for ec care in nonsurgical patients.…”
Section: Figurementioning
confidence: 99%
“…For squamous cell carcinoma, there are a few large retrospective and prospective cohort studies, that describe the distribution pattern of lymph node metastases (3,9,11,13,27). Most patients in these studies have T3 cancers and almost 60% has positive lymph nodes.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…The distribution pattern of lymph node metastases of esophageal cancer is unpredictable. Distribution of lymph node metastases may depend on tumor characteristics such as tumor location, histology, T-stage and the use of neoadjuvant therapy (9)(10)(11)(12)(13)(14). The surgical strategy should depend on the distribution pattern of nodal metastases but there is no worldwide consensus on the extent of lymphadenectomy.…”
Section: Introductionmentioning
confidence: 99%